Legal Protection for Roller Coaster Users Who Suffer from Safety Device Failure in Amusement Parks - Simbolon, Mhd Hilman Hawli; Adiwibowo, Yusuf; Kusuma, Ajeng Pramesthy Hardiani (Jurnal Justiciabelen, 2024)
Tourism has been a major focus in Indonesia's development policy since its inception, due to its natural, cultural, and historical wealth. The development of the times shows people's interest in tourism at affordable prices, one of which is a roller coaster. Roller coasters are exciting game rides with high speeds and challenging spins. In Indonesia, some places like Jatim Park and Dunia Fantasi offer roller coasters. Jember Regency, in particular, has great potential due to its diverse tourist destinations and significant visitor population, including immigrants from outside the city. However, the installation of roller coasters must pay attention to the readiness factor of the ride and weather factors for user safety. The Tourism Act and the Consumer Protection Act provide the right to comfort, security, and safety. However, often amusement parks lack clear readiness and regulations regarding the safety of visitors and often malfunction or failure of safety equipment on high-risk rides in amusement parks. Based on the analysis and discussion of the problems carried out in this thesis, it can be concluded that, First, tourists have the right to get legal protection and compensation based on existing legal rules. Both parties managing the amusement park must be responsible for matters that harm visitors, both material and non-material. Third, accidents in tourist attractions with high-risk activities are real risks. The causes include carelessness of the manager, lack of safety facilities, and visitor behavior. Many tourist attraction managers focus more on profits than on the safety of visitors, ignoring the obligations regulated in the Tourism Law and UUPK.